Pendayagunaan Teknologi di Klaster Komponen Kapal Desa Kebasen, Kecamatan Talang, Kabupaten Tegal - Haq, Alifya Arinal (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2013)
The Central Java government uses a cluster growth approach to develop small industrial sector. Cluster development constitutes one of many concerns in local economic growth. Tegal has some clusters, one of them is ship components cluster in Kebasen Village, Talang Sub-District. Cluster has many problems related to technology which hampers its development. The goal of this research is to review the utilization of technology in ship components cluster in Kebasen Village, Talang Sub-District, Tegal District. This research is a quantitative research where the analysis method uses qualitative descriptive and quantitative descriptive (scoring and t-test). The result of research is the level of technology utilization in this cluster is counted low. This cluster is yet to require a high technology due to some factors, including production necessity which is in small and medium enterprise, economic condition and human resources of workers. The technology utilization in the cluster uses manual production and manual electric equipments.